ZAKAT AS PUBLIC FINANCE IN INDONESIA? - Dharma, Budhi (Jurnal Kommunity Online, 2023)
The current situation shows that government is facing a dilemmatic situation where Indonesia’s government has an ambitious mission to increase their income through several channels under Joko Widodo’s administration. This mission is based on the willingness of Joko Widodo to catch up development in various sectors, in particular, infrastructure and local and underdeveloped regions. Besides that, Indonesia also wants to protect and empower 10 percent population which are categorized as poor people. To support this initiative, government endeavor increasing income through several channels such as tax amnesty, boosted income tax and increasing government's debt (MFI 2018). OECD (2016c) highlights that Indonesia's revenue should be increased since it has strong relationships with public and welfare provisions (p. 24)